STRATEGI PEMERINTAH DAERAH DALAM MENGEMBANGKAN OBJEK WISATA DI KABUPATEN BOLAANG MONGONDOW UTARA - .., Bustamin; Sambiran, Sarah; Rondonuwu, Arpi (Sam Ratulangi University, 2017)
AbstractEach region in Indonesia has a unique in terms of beauty and customs that exist in the area so as to attract tourists to visit it. To enhance the role of tourism, it is closely related among the goods in the form of own attractions that can be sold by means and infrastructure that support it related in the tourism industry. Enterprises to develop a tourist destination should pay attention to various factors that affect the existence of a tourist destination. North Sulawesi Province which used to have the nickname